2022
DOI: 10.3390/ijerph19148757
|View full text |Cite
|
Sign up to set email alerts
|

Highly Educated Immigrant Workers’ Perspectives of Occupational Health and Safety and Work Conditions That Challenge Work Safety

Abstract: This study explored the perspectives of new immigrant workers regarding occupational health and safety and workplace conditions that increase workers’ vulnerability to sustaining injury or illness. Using an interpretive research approach and semi-structured qualitative interviews, 42 new immigrant workers from a range of industries operating in two cities in a province in Canada were interviewed. Seventy-nine percent of the workers were highly qualified. A constant comparative approach was used to identify key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…High-quality and accessible training that is tailored to NIWs' needs and abilities has the potential to mitigate the personal barriers (eg, language and immigration status) identified in this study. 25 However, this study illustrates the poor accessibility and quality of OH&S training for NIWs in Alberta. In this study, the capitalist nature of the Canadian economy and the workplace culture were identified as contextual factors that influence OH&S training's accessibility and quality.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…High-quality and accessible training that is tailored to NIWs' needs and abilities has the potential to mitigate the personal barriers (eg, language and immigration status) identified in this study. 25 However, this study illustrates the poor accessibility and quality of OH&S training for NIWs in Alberta. In this study, the capitalist nature of the Canadian economy and the workplace culture were identified as contextual factors that influence OH&S training's accessibility and quality.…”
Section: Discussionmentioning
confidence: 75%
“…NIWs experience a number of personal barriers to exercising their OH&S rights, which are exacerbated by the systems and workplace culture that create unbalanced power dynamics. High-quality and accessible training that is tailored to NIWs' needs and abilities has the potential to mitigate the personal barriers (eg, language and immigration status) identified in this study 25 . However, this study illustrates the poor accessibility and quality of OH&S training for NIWs in Alberta.…”
Section: Discussionmentioning
confidence: 80%
“…PPE equipment was not provided ( 20 , 23 ) or needed to be purchased “out of pocket” in the case of migrant women hotel housekeepers ( 75 ) and there were reports of a lack of workplace ergonomic adaptation for women ( 23 ). Shankar et al ( 83 ) report that when OSH training did occur, workplace bullying, and harassment were not recognized as WRIs.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding working conditions, as women, migrant workers reportedly faced increased risk of workplace harassment and sexual harassment, including from supervisors ( 20 , 21 , 83 ) along with discrimination and dismissal due to pregnancy ( 20 ). These risks occurred alongside the reported lack of OSH acknowledgement of bullying and harassment as WRIs ( 83 ) as outlined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation